(untitled) (Semiárida, 2020)
The leaf epidermis of the following forbs from the Westem Chaco region (San Luis Province, Argentina) are analized and lIIustrated: Conyza bonariensis, Schkuria pinnata, Xanthium spinosum, Cryptantha mendocina, Evolvulus seticeus, Cucurbitella asperata, Ibicella parodii, Clematis denticulata, Solanum juvenale y Tribulus terrestris. The characteres used for taxonomíc determination are those useful for the identification of small fragments such as: cell walls, trichomas, stomata and cuticular omamentatlon. A key for the identification of these species is presented.